Computer incident response team for information security (CSIRT UPEC) - Chamorro Pantoja, Anderson Daniel; Pupiales Chacón, Silvia Verónica; Hidalgo Guijarro , Jairo Vladimir (SATHIRI, 2023)
All digital information is constantly exposed to incidents or vulnerabilities. The present investigation establishes the necessary resources for the conformation of a computer incident response team (CSIRT) at the State Polytechnic University of Carchi, (Ecuador), the CISRT-UPEC, is integrated by professional experts in the area of computer networks and computer security and also by technological teams with the purpose of providing support and assistance in information security issues especially in the educational units and sectional governments of the province of Carchi; the work contains documentary and field research for the analysis and interpretation of the data, and a qualitative approach to obtain research realities from other CSIRT in Ecuador, in addition, a convenience sample was generated to establish the services, policies and operational processes for the CSIRT-UPEC. As a result of the research, the CSIRT-UPEC is formed, with the establishment of the mission, vision and values as institutional identity, in addition to four services, eight policies, five operational processes and a service level agreement (SLA) for the start of its activities. At the moment, the enabling, operation and functioning of CSIRT-UPEC in the institution is being managed, with the association to the Computer Incident Response Center of the Telecommunications Regulation and Control Agency - EcuCERT of Arcotel and the group of computer incident response centers CSIRT of Ecuador.
Keywords: computer incidents; information security; digital information